Global Trends in Spiritual and Palliative Intervention in Cancer Patients: Bibliometric Analysis - Sukwan Sumono; Erna Rochmawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Advanced cancer patients often experience multidimensional suffering known as